Coated graphite negative electrode material and preparation method thereof

By using polymer materials, micro-nanographite materials and amine-based pore-forming agents on graphite negative electrode materials, the problems of lithium extraction and insufficient high-temperature performance during fast charging are solved, and the electrochemical performance of the battery is improved. Safety and reduce production costs.

CN119133410APending Publication Date: 2024-12-13SHIJIAZHUANG SHANGTAI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325790.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the fast charging process, the existing graphite negative electrode materials have lithium-ionized phenomena due to poor conductivity of the cladding layer, resulting in an uneven lithium metal layer, affecting the safety and capacity of the battery. The high-temperature performance of the composite material is insufficient, which limits the cycling performance of the battery. .

Method used

Using polymer materials, micro-nanographite materials and amine-based pore-forming agents as the coating components, the coating layer with excellent conductivity is formed through liquid phase coating and heat treatment, reducing crystallization, increasing the circulation channels of lithium ions, and improving Electrochemical properties and reduce production costs.

Benefits of technology

It improves the fast charging performance and discharge power of graphite negative electrode materials, avoids lithium extraction, enhances the safety and circulation performance of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133410A_ABST
    Figure CN119133410A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of graphite negative electrode materials, and particularly discloses a coated graphite negative electrode material and a preparation method thereof. The coated graphite negative electrode material comprises a micron graphite material and a coating layer, wherein the coating layer comprises the following raw materials: a high polymer material and a micro-nano graphite material of which La is less than or equal to 25nm; the micro-nano graphite material is loaded on the high polymer material; the coating layer is coated on the surface of the micron graphite material. The micro-nano graphite material has excellent conductivity, so that the fast charge performance and the discharge power can be improved, and lithium precipitation is avoided; the micro-nano graphite material disrupts the structure of a high polymer material in the coating layer, so that lithium ions can shuttle in the coating layer, the circulation channels of the lithium ions are increased, and the electrochemical performance of the graphite negative electrode material is improved; the micro-nano graphite material has extremely small expansibility in the charging and discharging process, does not damage the structure of the coating layer after being used for a long time, can improve the coating rate of the coating layer on the micro-nano graphite material, and reduces the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphite negative electrode materials, and in particular to a coated graphite negative electrode material and a preparation method thereof. Background Art

[0002] Graphite negative electrode materials are composed of carbon atoms and present a hexagonal honeycomb structure. They have high lithium storage capacity and good cycle performance, and can reduce the charge and discharge voltage of the battery. Therefore, they have been widely used in lithium-ion batteries. The coating process is a common process to improve the fast charging performance and low temperature performance of graphite negative electrode materials. In recent years, with the rapid development of new energy vehicles, fast-charging graphite negative electrode materials have gradually become the focus of attention in the lithium-ion battery negative electrode industry. In order to improve the fast charging performance and surface defects of graphite negative electrode materials, the existing coating materials are mainly based on asphalt, and some resin polymers are compounded as protective agents. The current preparation method of coated graphite negative electrode materials is to coat the coating material on the graphite surface, and then form a layer of soft carbon or hard carbon material on the graphite surface through high-temperature carbonization.

[0003] However, after being coated with asphalt composite materials, the conductivity of graphite particles will be reduced to a certain extent due to the presence of the coating layer (the conductivity of soft carbon or hard carbon materials is worse than that of graphite), resulting in lithium precipitation during fast charging, causing part of the metallic lithium to precipitate on the graphite surface to form an uneven lithium metal layer. This uneven lithium metal layer not only poses a serious safety hazard, but also aggravates the growth of the solid electrolyte interface film, causing the active lithium to be trapped in it and become "dead lithium", unable to participate in the subsequent lithium insertion and extraction cycle, resulting in a significant attenuation of the battery capacity and an adverse effect on the fast charging performance. Therefore, there is an urgent need to develop a coating with a unique composition (and structure) to improve the electrochemical properties of graphite negative electrode materials. Summary of the invention

[0004] In view of the above problems, the present invention provides a coated graphite negative electrode material and a preparation method thereof. The present invention improves the fast charging performance of the graphite negative electrode material by improving the composition and structure of the coating layer.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is: In a first aspect, the present invention provides a coated graphite negative electrode material, comprising a micron graphite material and a coating layer, wherein the coating layer comprises the following raw materials: a polymer material and a micro-nano graphite material; The micro-nano graphite material is loaded on the polymer material; the coating layer is coated on the surface of the micron graphite material; and the average width of the graphite crystals of the micro-nano graphite material along the crystal A axis is ≤25nm.

[0006] It should be noted that the average width (La) of the graphite crystal along the crystal A axis is ≤25nm, indicating that the micro-nano graphite material is isotropic, that is, the micro-nano graphite material is ordered at the micron level structure, but is in a disordered state in the entire coated graphite negative electrode material.

[0007] Compared with the prior art, the coated graphite negative electrode material provided by the present invention uses micron graphite material as the main material of the coated graphite negative electrode material, and the surface is coated with a coating layer of a composite of multiple materials. The introduction of specific La micro-nano graphite material reduces the crystallization of the coating layer, improves the degree of disorder of the coating layer, increases the deionization effect of lithium ions during the embedding process, and improves the fast charging performance of the micron graphite material.

[0008] The present invention adds a micro-nano graphite material with specific La into the coating layer, which has excellent electrical conductivity, can improve the fast charging and discharge power of the graphite negative electrode material, avoid the occurrence of lithium precipitation, and is safer to use; adding the micro-nano graphite material into the polymer material can disrupt the structure of the polymer material in the coating layer, which is beneficial for lithium ions to shuttle in the coating layer, that is, the circulation channel of lithium ions is increased, the circulation rate of lithium ions is accelerated, and the electrochemical performance of the graphite negative electrode material is improved; the micro-nano graphite material has extremely small expansion during the charging and discharging process, and long-term use will not damage the structure of the coating layer; in addition, the addition of the micro-nano graphite material can greatly improve the coating rate of the coating layer on the micron graphite material, thereby reducing the production cost.

[0009] Preferably, the coating layer further comprises an amine pore-forming agent, and the amine pore-forming agent is loaded on the polymer material.

[0010] The present invention adds an amine pore-forming agent to the coating layer to adjust the surface functional groups of the coating layer to achieve element doping, thereby improving the contact compatibility between the coating layer and the electrolyte, so that the coated graphite negative electrode material has good wettability in the electrolyte, and the electrolyte can better penetrate and distribute in the entire battery, thereby promoting the rapid transmission of lithium ions and improving the charging and discharging efficiency of the lithium battery; the amine pore-forming agent will form a thinner SEI film (solid electrolyte interface film) during the charging and discharging process of the lithium battery, while improving the conductivity, fast charging performance and high-rate discharge performance of the graphite negative electrode material, reducing the consumption of active substances; in addition, the amine pore-forming agent will undergo thermal decomposition under high temperature conditions to produce certain pores, which can disrupt the structure of the polymer material in the coating layer, which is beneficial for lithium ions to shuttle in the coating layer, that is, increase the circulation channel of lithium ions, accelerate the circulation rate of lithium ions, and thus improve the electrochemical performance of the graphite negative electrode material.

[0011] For example, the coated graphite negative electrode material is obtained by liquid phase coating and heat treatment.

[0012] Preferably, the coated graphite negative electrode material comprises raw materials in the following percentages: 82% to 98% of micron graphite material, 0.1% to 5% of micro-nano graphite material, 1% to 10% of polymer material and 0.1% to 3% of amine pore former.

[0013] The present invention can better exert the synergistic effect of each raw material by limiting the content of each raw material, obtain a coated graphite negative electrode material with a specific structure, maximize the electrochemical performance of the graphite negative electrode material, and save the cost of raw materials. When a polymer material is used as a coating material, the residual carbon content of the polymer material after heat treatment is small. If the amount added is too small, the micron graphite material cannot be coated. If the amount added is too large, it will cause uneven local coating and a significant increase in production costs. The carbon content of the micro-nano graphite material is basically unchanged before and after the heat treatment. The present invention creatively adds micro-nano graphite materials to the polymer material, which can greatly increase the residual carbon content of the coating layer after the heat treatment. A relatively small amount of polymer material can be used to achieve complete coating of the micron graphite material, thereby reducing production costs.

[0014] Preferably, the method for preparing the micro-nano graphite material comprises the following steps: The isotropic coke powder is subjected to high temperature treatment at 2800° C. to 3200° C. to obtain the micro-nano graphite material.

[0015] The present invention uses isotropic coke powder as raw material and performs high temperature treatment at a specific temperature to prepare isotropic (La≤25nm) micro-nano graphite material. Compared with graphene or carbon micro-nanotubes, micro-nano graphite material itself does not have bending or curling, so it will not reduce the tap density and compaction density of the coated material (coated graphite negative electrode material), ensuring the processability of the coated material, such as the solid content will not be reduced, and the risk of clogging the filter element is reduced; in addition, ensuring the compaction density of the material plays a decisive role in maintaining the volume energy density of the battery cell.

[0016] Further preferably, the particle size of the isotactic coke powder is 1 μm to 1.5 μm.

[0017] More preferably, the temperature is raised to 2800°C-3200°C by programmed heating, with a heating rate of 1°C / min-20°C / min.

[0018] Further preferably, the high temperature treatment time is 0.5h~5h.

[0019] For example, after the high temperature treatment, crushing is also included to prevent the micro-nano graphite material from sticking.

[0020] Preferably, the particle size of the micro-nano graphite material is 0.1 nm to 1 μm.

[0021] Preferably, the particle size of the micron graphite material is 5 μm to 20 μm.

[0022] For example, the micron graphite material is selected from at least one of artificial graphite and natural graphite; the particle type can be primary particles or secondary particles.

[0023] Preferably, the polymer material is selected from at least one of asphalt, phenolic resin, acrylamide, polyethylene, polyamide, polyurethane or polysulfide rubber.

[0024] The present invention uses a polymer material as a carrier of the coating layer, and the polymer material can be mixed more evenly with the ultra-microstructured graphite and the amine pore-forming agent under liquid phase conditions. The present invention does not limit the specific type of the above polymer material, and the coated graphite negative electrode material provided by the present invention is applicable to all the above polymer materials.

[0025] Preferably, the amine pore-forming agent is selected from at least one of ammonium bicarbonate, ammonium carbonate, ammonium hydrogen borate, ammonium borate, ammonium hydrogen phosphate, ammonium phosphate, ammonium hydrogen sulfate or ammonium sulfate.

[0026] The preferred amine pore-forming agent of the present invention contains elements such as N, P, S, and P, which have a good regulating effect on the wettability of the electrolyte and the formation of the SEI film on the surface of the negative electrode. Elements such as N, P, S, and P are also the main components of the SEI film. Adding the preferred amine pore-forming agent to the coating layer can reduce the consumption of active substances in the electrolyte and reduce the thickness of the SEI film. The SEI film itself is not conductive. If it is too thick, it will have an adverse effect on the conductive performance. After the thickness of the SEI film is reduced, the conductive performance, fast charging performance, and high-rate discharge performance of the graphite negative electrode material can be improved.

[0027] In a second aspect, the present invention provides a method for preparing a coated graphite negative electrode material, comprising the following steps: S1, making a polymer material into a liquid phase, adding micro-nano graphite material to obtain a coating layer mixed solution; S2, mixing the coating layer mixed solution with the micron graphite material, drying, heat treating, and depolymerizing to obtain a coated graphite negative electrode material.

[0028] Preferably, S1, the polymer material is made into a liquid phase, and micro-nano graphite material and an amine pore-forming agent are added to obtain a coating layer mixed solution.

[0029] The method for preparing the coated graphite negative electrode material provided by the present invention adopts liquid phase coating, the coating layer is more uniform, the performance of the coated material is better, and the quality is more stable.

[0030] Preferably, in S1, the method of making the polymer material into a liquid phase comprises: heating and melting the polymer material to obtain a liquid polymer material.

[0031] For example, in S1, the heating and melting temperature is 60°C to 200°C.

[0032] Preferably, in S1, the method of making the polymer material into a liquid phase comprises: adding the polymer material into a solvent to obtain a polymer material solution with a viscosity of 1 MPa·s to 100 MPa·s.

[0033] Further preferably, in S1, the solvent is selected from at least one of water, acetone, N-methylpyrrolidone or ethanol.

[0034] For example, in S2, the drying is selected from spray drying, blast drying or rotary kiln drying.

[0035] Preferably, in S2, the heat treatment comprises the following steps: heating the dried mixture to 100°C to 500°C at a rate of 1°C / min to 15°C / min, and keeping the temperature for 10min to 80min.

[0036] Preferably, in S2, the heat treatment comprises the following steps: heating the dried mixed material to 500°C~1600°C at a rate of 2°C / min~20°C / min, and keeping the temperature for 0.5h~10h.

[0037] The present invention can select the type of heat treatment according to product requirements. Low-temperature heat treatment (100°C~500°C) will only cause most of the volatile components to escape, while most of the polymer materials, micro-nano graphite materials and amine pore-forming agent components will remain, which can maintain the properties before low-temperature treatment, cover up a large number of defects in micron graphite materials, have few side reactions, reduce lithium consumption, and improve long-cycle performance, which is suitable for long-cycle products. High-temperature heat treatment (500°C~1600°C) can increase the carbonization degree of the coating material, improve conductivity, and enhance dynamics, and is suitable for fast-charging materials.

[0038] It should be noted that the length of the insulation time can be adjusted routinely according to the instruments and equipment used.

[0039] For example, in S2, the depolymerization is completed in a depolymerization machine. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of the structure of the coated graphite negative electrode material provided by the present invention; Among them, 1 represents micron graphite material, 2 represents micro-nano graphite material, 3 represents polymer material, 4 represents pores, and the curve represents the graphite layer. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] refer to Figure 1 The present invention provides a coated graphite negative electrode material, comprising a micron graphite material 1 and a coating layer, wherein the coating layer contains the following raw materials: a polymer material 3, a micro-nano graphite material 2 and an amine pore-forming agent; The micro-nano graphite material 2 and the amine pore-forming agent are loaded on the polymer material 3; the coating layer is coated on the surface of the micron graphite material 1; and the average width of the graphite crystals of the micro-nano graphite material along the crystal A axis is ≤25nm.

[0043] Amine pore formers will undergo pyrolysis after heat treatment to form a part of the pores4; graphite material is highly ordered carbon, with a microscopic arrangement of carbon atoms stacked layer by layer ( Figure 1 represented as a curve in the figure).

[0044] Unless otherwise specified in the present invention, percentages all represent mass content.

[0045] In order to better illustrate the present invention, further examples are given below.

[0046] Example 1 This embodiment provides a coated graphite negative electrode material (see Figure 1 ), which is composed of the following raw materials in percentage: 90% of micron graphite material with a particle size of 10μm~12μm, 3% of micro-nano graphite material with a particle size of 0.5nm~0.6μm, 5% of polymer material and 2% of amine pore-forming agent.

[0047] The micron graphite material is the main material, and the polymer material, the micro-nano graphite material and the amine pore-forming agent together form the coating layer. The micro-nano graphite material and the amine pore-forming agent are loaded on the polymer material; and the coating layer is coated on the surface of the micron graphite material.

[0048] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, the isotropic coke powder with a particle size of 1μm~1.2μm is heated to 3000℃ at a rate of 8℃ / min for high temperature treatment and kept at this temperature for 3h to obtain a micro-nano graphite material with La=21nm.

[0049] Sb, weigh according to the designed ratio of the raw materials, heat and melt the polymer material, add micro-nano graphite material and amine pore-forming agent to the obtained liquid polymer material, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0050] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 300°C at a rate of 10°C / min for low-temperature treatment, and kept warm for 50 minutes; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0051] The specific ingredients of this example are shown in Table 1.

[0052] Example 2 This embodiment provides a coated graphite negative electrode material (see Figure 1 ), which is composed of the following raw materials in percentage: 85% of micron graphite material with a particle size of 12μm~15μm, 6% of micro-nano graphite material with a particle size of 0.3nm~0.4μm, 8% of polymer material and 1% of amine pore-forming agent.

[0053] The micron graphite material is the main material, and the polymer material, the micro-nano graphite material and the amine pore-forming agent together form the coating layer. The micro-nano graphite material and the amine pore-forming agent are loaded on the polymer material; and the coating layer is coated on the surface of the micron graphite material.

[0054] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, the isotropic coke powder with a particle size of 1.2μm~1.4μm was heated to 3200℃ at a rate of 15℃ / min for high temperature treatment and kept at this temperature for 5h to obtain a micro-nano graphite material with La=23nm.

[0055] Sb, weigh according to the designed ratio of the raw materials, heat and melt the polymer material, add micro-nano graphite material and amine pore-forming agent to the obtained liquid polymer material, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0056] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 400°C at a rate of 8°C / min for low-temperature treatment, and kept warm for 40 minutes; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0057] The specific ingredients of this example are shown in Table 1.

[0058] Example 3 This embodiment provides a coated graphite negative electrode material (see Figure 1 ), which is composed of the following raw materials in percentage: 93% of micron graphite material with a particle size of 15μm~18μm, 1% of micro-nano graphite material with a particle size of 0.7nm~0.8μm, 4.5% of polymer material and 1.5% of amine pore-forming agent.

[0059] The micron graphite material is the main material, and the polymer material, the micro-nano graphite material and the amine pore-forming agent together form the coating layer. The micro-nano graphite material and the amine pore-forming agent are loaded on the polymer material; and the coating layer is coated on the surface of the micron graphite material.

[0060] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, the isotropic coke powder with a particle size of 1.3μm~1.5μm is heated to 2800℃ at a rate of 1℃ / min for high temperature treatment and kept at this temperature for 0.8h to obtain a micro-nano graphite material with La=18nm.

[0061] Sb, weigh according to the designed ratio of the raw materials, heat and melt the polymer material, add micro-nano graphite material and amine pore-forming agent to the obtained liquid polymer material, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0062] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 1000°C at a rate of 10°C / min for high-temperature treatment, and kept warm for 3 hours; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0063] The specific ingredients of this example are shown in Table 1.

[0064] Example 4 This embodiment provides a coated graphite negative electrode material (see Figure 1 ), which is composed of the following raw materials in percentage: 98% of micron graphite material with a particle size of 5μm~8μm, 0.6% of micro-nano graphite material with a particle size of 0.1nm~2μm, 1% of polymer material and 0.4% of amine pore-forming agent.

[0065] The micron graphite material is the main material, and the polymer material, the micro-nano graphite material and the amine pore-forming agent together form the coating layer. The micro-nano graphite material and the amine pore-forming agent are loaded on the polymer material; and the coating layer is coated on the surface of the micron graphite material.

[0066] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, the isotropic coke powder with a particle size of 1.1μm~1.3μm was heated to 3200℃ at a rate of 20℃ / min for high temperature treatment and kept at this temperature for 4h to obtain a micro-nano graphite material with La=22nm.

[0067] Sb, weigh according to the designed ratio of the raw materials, heat and melt the polymer material, add micro-nano graphite material and amine pore-forming agent to the obtained liquid polymer material, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0068] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 1300°C at a rate of 15°C / min for high-temperature treatment, and kept warm for 2 hours; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0069] The specific ingredients of this example are shown in Table 1.

[0070] Example 5 This embodiment provides a coated graphite negative electrode material (see Figure 1 ), composed of the following raw materials in percentage: 97.8% of micron graphite material with a particle size of 17μm~20μm, 0.1% of micro-nano graphite material with a particle size of 0.8nm~1μm, 2% of polymer material and 0.1% of amine pore-forming agent.

[0071] The micron graphite material is the main material, and the polymer material, the micro-nano graphite material and the amine pore-forming agent together form the coating layer. The micro-nano graphite material and the amine pore-forming agent are loaded on the polymer material; and the coating layer is coated on the surface of the micron graphite material.

[0072] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, same as Example 1, no further details are given.

[0073] Sb, weigh according to the designed ratio of the raw materials, add the polymer material into the solvent, add the micro-nano graphite material and the amine pore-forming agent into the obtained polymer material solution with a viscosity of 80 MPa·s, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0074] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 100°C at a rate of 1°C / min for low-temperature treatment, and kept warm for 80 minutes; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0075] The specific ingredients of this example are shown in Table 1.

[0076] Example 6 This embodiment provides a coated graphite negative electrode material (see Figure 1 ), which is composed of the following raw materials in percentage: 82% of micron graphite material with a particle size of 7μm~9μm, 5% of micro-nano graphite material with a particle size of 0.3nm~0.5μm, 10% of polymer material and 3% of amine pore-forming agent.

[0077] The micron graphite material is the main material, and the polymer material, the micro-nano graphite material and the amine pore-forming agent together form the coating layer. The micro-nano graphite material and the amine pore-forming agent are loaded on the polymer material; and the coating layer is coated on the surface of the micron graphite material.

[0078] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, same as Example 1, no further details are given.

[0079] Sb, weigh according to the designed ratio of the raw materials, add the polymer material into the solvent, add the micro-nano graphite material and the amine pore-forming agent into the obtained polymer material solution with a viscosity of 50 MPa·s, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0080] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 550°C at a rate of 2°C / min for high-temperature treatment, and kept warm for 8 hours; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0081] The specific ingredients of this example are shown in Table 1.

[0082] Example 7 The present embodiment provides a coated graphite negative electrode material, which is composed of the following raw materials in percentage: 90% of micron graphite material with a particle size of 10 μm to 12 μm, 3% of micro-nano graphite material with a particle size of 0.5 nm to 0.7 μm, and 7% of polymer material.

[0083] The micron graphite material is the main material, and the polymer material and the micro-nano graphite material together form the coating layer. The micro-nano graphite material is loaded on the polymer material; the coating layer is coated on the surface of the micron graphite material.

[0084] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, same as Example 1, no further details are given.

[0085] Sb, weigh according to the designed ratio of the raw materials, add the polymer material into the solvent, add the micro-nano graphite material into the obtained polymer material solution with a viscosity of 2MPa·s, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0086] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 480°C at a rate of 15°C / min for low-temperature treatment, and kept warm for 18 minutes; then it is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0087] The specific ingredients of this example are shown in Table 1.

[0088] Example 8 The present embodiment provides a coated graphite negative electrode material, which is composed of the following raw materials in percentage: 92% of micron graphite material with a particle size of 10 μm to 15 μm, 4% of micro-nano graphite material with a particle size of 0.6 nm to 0.8 μm, and 4% of polymer material.

[0089] The micron graphite material is the main material, and the polymer material and the micro-nano graphite material together form the coating layer. The micro-nano graphite material is loaded on the polymer material; the coating layer is coated on the surface of the micron graphite material.

[0090] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, same as Example 1, no further details are given.

[0091] Sb, weigh according to the designed ratio of the raw materials, add the polymer material into the solvent, add the micro-nano graphite material into the obtained polymer material solution with a viscosity of 100 MPa·s, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0092] Sc, the coating layer mixed solution is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 1600°C at a rate of 20°C / min for high-temperature treatment, and the temperature is kept for 35 minutes; then the mixed material is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0093] The specific ingredients of this example are shown in Table 1.

[0094] Comparative Example 1 This comparative example provides a graphite negative electrode material, which is obtained by low-temperature treatment of a micron graphite material with a particle size of 10 μm to 12 μm. The specific preparation method includes the following steps: The micron graphite material is placed in a high temperature furnace, heated to 300°C at a rate of 10°C / min for low temperature treatment, and kept warm for 50 minutes; then placed in a depolymerization machine for depolymerization, sieved, and a graphite negative electrode material is obtained.

[0095] Comparative Example 2 This comparative example provides a coated graphite negative electrode material, the raw materials of which are composed of 93% of micron graphite material with a particle size of 15 μm to 18 μm and 7% of phenolic resin.

[0096] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: The raw materials are weighed according to the designed ratio, the phenolic resin is heated and melted at 60°C, the liquid phenolic resin is sprayed into the micron graphite material through a high-speed nozzle, and dispersed evenly by high-speed stirring. The obtained mixed material is dried and transferred to a high-temperature furnace, and the temperature is increased to 1000°C at a rate of 10°C / min for high-temperature treatment, and the temperature is kept for 3 hours; then the material is placed in a depolymerizer for depolymerization, sieved, and a coated graphite negative electrode material is obtained.

[0097] Comparative Example 3 This comparative example provides a coated graphite negative electrode material, the raw materials of which are composed of 90% of micron graphite material with a particle size of 10 μm to 12 μm and 10% of micro-nano graphite material with a particle size of 0.5 nm to 0.6 μm.

[0098] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, same as Example 1, no further details are given.

[0099] Sb, weigh according to the designed ratio of the raw materials, stir and disperse the micron graphite material and the micro-nano graphite material at high speed, transfer the obtained mixed material to a high-temperature furnace, heat it to 300°C at a rate of 10°C / min for low-temperature treatment, and keep it warm for 50 minutes; then put it into a depolymerizer for depolymerization, sieve it, and obtain a coated graphite negative electrode material.

[0100] Comparative Example 4 This comparative example provides a coated graphite negative electrode material, which is composed of the following raw materials in percentage: 90% of micron graphite material with a particle size of 10μm-12μm, 8% of asphalt and 2% of amine pore-forming agent.

[0101] The micron graphite material is the main material, and the asphalt and the amine pore-forming agent together form the coating layer. The amine pore-forming agent is loaded on the asphalt; and the coating layer is coated on the surface of the micron graphite material.

[0102] The method for preparing the above-mentioned coated graphite negative electrode material comprises the following steps: Sa, weigh the raw materials according to the designed ratio, heat and melt the asphalt at 120°C, add amine pore-forming agent to the obtained liquid asphalt, stir at high speed to disperse evenly, and obtain a coating layer mixed solution.

[0103] Sb is the same as Sc in Example 1 and will not be described in detail.

[0104] Comparative Example 5 This comparative example provides a coated graphite negative electrode material, which is similar to Example 1, except that the micro-nano graphite material is replaced with a micro-nano graphite material of equal mass that does not have anisotropy. The remaining conditions are the same as those in Example 1 and will not be described in detail.

[0105] The micro-nano graphite material in this comparative example has La=30nm, and is obtained by directly grinding micron graphite material.

[0106] Electrochemical performance test In order to verify the electrochemical properties of the coated graphite negative electrode material provided by the present invention, the negative electrode materials provided by Examples 1 to 8 of the present invention and Comparative Examples 1 to 5 were prepared into button batteries, and the button batteries were subjected to performance tests. During the test, the battery was first discharged to 0.005V at 0.1C, left to stand for 10 minutes, and then charged to 2V at 0.1C for 5 cycles; then a 3C rate charge and discharge test was performed, with a voltage range of 0.005V to 2V, constant current and constant voltage charging for charging, and constant current discharge for discharging, and the rate capacity after 5 cycles was tested, respectively, and the test results are shown in Table 1.

[0107] The method for preparing a button cell comprises the following steps: The negative electrode materials of the embodiment and the comparative example were mixed with the conductive agent and the binder at a high speed, respectively, the mass ratio of the negative electrode material, the conductive agent and the binder was 80%:10%:10%, and a proper amount of NMP was added to prepare a viscous slurry with a viscosity of 500mPa·s~9000mPa·s. The viscous slurry was evenly coated on the copper foil with a surface density of 1mg / cm 2 ~2mg / cm 2 , then dried at 105°C for 6h, sliced ​​to obtain a small disc electrode; in a glove box, the small disc electrode and the lithium metal disc were assembled into a button battery.

[0108] Table 1 Raw material components of coated graphite negative electrode materials in Example Electrochemical performance of negative electrode materials of embodiments and comparative examples

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A coated graphite negative electrode material, characterized in that: It includes a micron graphite material and a coating layer, wherein the coating layer contains the following raw materials: a polymer material and a micro-nano graphite material; The micro-nano graphite material is loaded on the polymer material; the coating layer is coated on the surface of the micron graphite material; and the average width of the graphite crystals of the micro-nano graphite material along the crystal A axis is ≤25nm.

2. The coated graphite negative electrode material according to claim 1, characterized in that: The coating layer further comprises an amine pore-forming agent, and the amine pore-forming agent is loaded on the polymer material.

3. The coated graphite negative electrode material according to claim 2, characterized in that: The coated graphite negative electrode material comprises raw materials in the following percentages: 82% to 98% of micron graphite material, 0.1% to 5% of micro-nano graphite material, 1% to 10% of polymer material and 0.1% to 3% of amine pore-forming agent.

4. The coated graphite negative electrode material according to claim 1, characterized in that: The preparation method of the micro-nano graphite material comprises the following steps: The isotropic coke powder is heated to 2800°C-3200°C at a rate of 1°C / min-20°C / min for high temperature treatment and kept at this temperature for 0.5h-5h to obtain the micro-nano graphite material.

5. The coated graphite negative electrode material according to claim 4, characterized in that: The particle size of the micron graphite material is 5 μm to 20 μm; and / or The particle size of the micro-nano graphite material is 0.1 nm to 1 μm; and / or The particle size of the isotropic coke powder is 1 μm to 1.5 μm.

6. The coated graphite negative electrode material according to claim 2, characterized in that: The polymer material is selected from at least one of asphalt, phenolic resin, acrylamide, polyethylene, polyamide, polyurethane or polysulfide rubber; and / or The amine pore-forming agent is selected from at least one of ammonium bicarbonate, ammonium carbonate, ammonium hydrogen borate, ammonium borate, ammonium hydrogen phosphate, ammonium phosphate, ammonium hydrogen sulfate or ammonium sulfate.

7. The method for preparing the coated graphite negative electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, making a polymer material into a liquid phase, adding micro-nano graphite material to obtain a coating layer mixed solution; S2, mixing the coating layer mixed solution with the micron graphite material, drying, heat treating, and depolymerizing to obtain a coated graphite negative electrode material.

8. The method for preparing the coated graphite negative electrode material according to claim 7, characterized in that: S1, making the polymer material into a liquid phase, adding micro-nano graphite material and amine pore-forming agent to obtain a coating layer mixed solution.

9. The method for preparing the coated graphite negative electrode material according to claim 7 or 8, characterized in that: In S1, the method of making the polymer material into a liquid phase comprises: heating and melting the polymer material to obtain a liquid polymer material; or In S1, the method for making the polymer material into a liquid phase includes: adding the polymer material to a solvent to obtain a polymer material solution with a viscosity of 1 MPa·s to 100 MPa·s; the solvent is selected from at least one of water, acetone, N-methylpyrrolidone or ethanol.

10. The method for preparing the coated graphite negative electrode material according to claim 7 or 8, characterized in that: In S2, the heat treatment comprises the following steps: heating the dried mixed material to 100°C to 500°C at a rate of 1°C / min to 15°C / min, and keeping the temperature for 10min to 80min; or In S2, the heat treatment comprises the following steps: heating the dried mixed material to 500°C~1600°C at a rate of 2°C / min~20°C / min, and keeping the temperature for 0.5h~10h.